Welcome to our community

Be a part of something great, join today!

Problem of the week #69 - July 22nd, 2013

Status
Not open for further replies.
  • Thread starter
  • Admin
  • #1

Jameson

Administrator
Staff member
Jan 26, 2012
4,052
Without using a calculator and showing your work, simplify \(\displaystyle \frac1{\sqrt{12-2\sqrt{35}}}-\frac2{\sqrt{10+2\sqrt{21}}}-\frac1{\sqrt{8+2\sqrt{15}}}\).
--------------------
Remember to read the POTW submission guidelines to find out how to submit your answers!
 
  • Thread starter
  • Admin
  • #2

Jameson

Administrator
Staff member
Jan 26, 2012
4,052
Congratulations to the following members for their correct solutions:

1) MarkFL
2) anemone
3) soroban

Solution (from anemone):
First we notice that we can only rewrite the radicand (the sum of two terms) into the form \(\displaystyle \sqrt{m+k\sqrt{n}}=a+b\sqrt{n}\).

In another word, we could begin to simplify the last two terms first before we start to evaluate the given expression.

Let \(\displaystyle \sqrt{10+2\sqrt{21}}=a+b\sqrt{21}\).

Squaring both sides to solve for the values for \(\displaystyle a\) and \(\displaystyle b\) we get:

\(\displaystyle 10+2\sqrt{21}=a^2+21b^2+2ab\sqrt{21}\)

By equating the coefficient of the \(\displaystyle \sqrt{21}\) and also the constant we obtain:

\(\displaystyle a=\sqrt{7}\), \(\displaystyle b=\frac{1}{\sqrt{7}}\) and hence \(\displaystyle \sqrt{10+2\sqrt{21}}=\sqrt{7}+\left(\frac{1}{\sqrt{7}}\right)\sqrt{21}=\sqrt{7}+\sqrt{3}\).

We proceed in a similar fashion to simplify \(\displaystyle \sqrt{8+2\sqrt{15}}\) and get \(\displaystyle \sqrt{8+2\sqrt{15}}=\sqrt{5}+\sqrt{3}\).

Therefore, we now have

\(\displaystyle \frac{1}{\sqrt{12-2\sqrt{25}}}-\frac{2}{\sqrt{10+2\sqrt{21}}}-\frac{1}{\sqrt{8+2\sqrt{15}}}\)

\(\displaystyle =\frac{1}{\sqrt{12-2\sqrt{25}}}-\frac{2}{\sqrt{7}+\sqrt{3}}-\frac{1}{\sqrt{5}+\sqrt{3}}\)

What we could do now is to multiply top and bottom of all of these three terms by their conjugates and this yields

\(\displaystyle =\frac{\sqrt{12+2\sqrt{25}}}{(\sqrt{12-2\sqrt{25}})(\sqrt{12+2\sqrt{25}})}-\frac{2(\sqrt{7}-\sqrt{3})}{(\sqrt{7}+\sqrt{3})(\sqrt{7}-\sqrt{3})}-\frac{(1)(\sqrt{5}-\sqrt{3})}{(\sqrt{5}+\sqrt{3})(\sqrt{5}-\sqrt{3})}\)

\(\displaystyle =\frac{\sqrt{12+2\sqrt{25}}}{\sqrt{144-140}}-2\left(\frac{\sqrt{7}-\sqrt{3}}{7-3}\right)-\left(\frac{\sqrt{5}-\sqrt{3}}{5-3}\right)\)

\(\displaystyle =\frac{\sqrt{12+2\sqrt{25}}}{2}-2\left(\frac{\sqrt{7}-\sqrt{3}}{4}\right)-\left(\frac{\sqrt{5}-\sqrt{3}}{2}\right)\)

\(\displaystyle =\frac{\sqrt{12+2\sqrt{25}}}{2}-\left(\frac{\sqrt{7}-\sqrt{3}}{2}\right)-\left(\frac{\sqrt{5}-\sqrt{3}}{2}\right)\)

But we know we could simplify \(\displaystyle \sqrt{12+2\sqrt{25}}\) further to get \(\displaystyle \sqrt{12+2\sqrt{25}}=\sqrt{7}+\sqrt{5}\) and so

\(\displaystyle =\frac{\sqrt{7}+\sqrt{5}}{2}-\left(\frac{\sqrt{7}-\sqrt{3}}{2}\right)-\left(\frac{\sqrt{5}-\sqrt{3}}{2}\right)\)

\(\displaystyle =\frac{\sqrt{7}+\sqrt{5}-\sqrt{7}+\sqrt{3}-\sqrt{5}+\sqrt{3}}{2}\)

\(\displaystyle =\frac{2\sqrt{3}}{2}\)

\(\displaystyle =\sqrt{3}\)


Alternate solution (from soroban):
[tex] \text{Simplify: }\:x \;=\; \frac{1}{\sqrt{12-2\sqrt{35}}} - \frac{2}{\sqrt{10+2\sqrt{21}}} - \frac{1}{\sqrt{8+2\sqrt{15}}} [/tex]

Note that: .[tex]\begin{Bmatrix}12-2\sqrt{35} &=& (\sqrt{7}-\sqrt{5})^2 \\ 10 + 2\sqrt{21} &=& (\sqrt{7}+\sqrt{3})^2 \\ 8 + 2\sqrt{15} &=& (\sqrt{3}+\sqrt{5})^2 \end{Bmatrix}[/tex]


We have:
.. [tex]x \;=\;\frac{1}{\sqrt{7}-\sqrt{5}} - \frac{2}{\sqrt{7}+\sqrt{3}} - \frac{1}{\sqrt{3}+\sqrt{5}}[/tex]

. .[tex]x \;=\;\frac{\sqrt{7}+\sqrt{3})(\sqrt{3}+\sqrt{5}) - 2(\sqrt{7}-\sqrt{5})(\sqrt{3}+\sqrt{5}) - (\sqrt{7}-\sqrt{5})(\sqrt{7}+\sqrt{34})}{(\sqrt{7}-\sqrt{5})(\sqrt{7}+\sqrt{3})(\sqrt{3}+\sqrt{5})} [/tex]


The numerator is:

[tex]N_x \;=\;(\sqrt{7}+\sqrt{3})(\sqrt{3}+\sqrt{5}) - 2(\sqrt{7}-\sqrt{5})(\sqrt{3}+\sqrt{5}) - (\sqrt{7}-\sqrt{5})(\sqrt{7}+\sqrt{34}) [/tex]

. . . [tex]=\;\sqrt{21} + \sqrt{35} + 3 + \sqrt{15} - 2\sqrt{21} - 2\sqrt{35} + 2\sqrt{15} + 10 - 7 - \sqrt{21} + \sqrt{35} + \sqrt{15}[/tex]

. . . [tex]=\;6 + 4\sqrt{15} - 2\sqrt{21} \;=\;2\sqrt{3}(\sqrt{3} + 2\sqrt{5} - \sqrt{7})[/tex]


The denominator is:

[tex]D_x \;=\;(\sqrt{7}-\sqrt{5})(\sqrt{7}+\sqrt{3})(\sqrt{3}+\sqrt{5}) [/tex]

. . . [tex]=\;(\sqrt{7}-\sqrt{5})(\sqrt{21} + \sqrt{35} + 3 + \sqrt{15})[/tex]

. . . [tex]=\;7\sqrt{3} + 7\sqrt{5} + 3\sqrt{7} + \sqrt{105} - \sqrt{105} - 5\sqrt{7} - 3\sqrt{5} - 5\sqrt{3}[/tex]

. . . [tex]=\;2\sqrt{3} + 4\sqrt{5} - 2\sqrt{7} \;=\;2(\sqrt{3} + 2\sqrt{5} - \sqrt{7}) [/tex]


Therefore: .[tex]x \;=\;\frac{N_x}{D_x} \;=\;\frac{2\sqrt{3}(\sqrt{3}+2\sqrt{5}-\sqrt{7})}{2(\sqrt{3}+2\sqrt{5} - \sqrt{7})} \;=\; \sqrt{3}[/tex]
 
Status
Not open for further replies.